Exploring attitudinal shifts in students’ lifestyle and dietary habits: The impact of formal education in nutrition and dietetics - Boda Francisc-Andrei; Májai Erzsébet; Baricsán Johanna; Boda Hajnalka; Kovács Béla (Acta Marisiensis - Seria Medica)
Objective: The study aimed to evaluate the lifestyle and dietary habit changes among students enrolled in the Nutrition and Dietetics program at the George Emil Palade University of Medicine, Pharmacy, Science, and Technology of Târgu Mureș. Specifically, we examined the influence of academic progression on stress levels, dietary choices, purchasing habits, and physical activity.